First observation and amplitude analysis of the B- → D+K-π-decay - Aaij, Roel; Adeva, B.; Adinolfi, M.; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; et al. (Physical review. D, Particles, fields, gravitation, and cosmology, 2015)
The B−→D+K−π− decay is observed in a data sample corresponding to 3.0 fb−1 of pp collision data recorded by the LHCb experiment during 2011 and 2012. Its branching fraction is measured to be B(B−→D+K−π−)=(7.31±0.19±0.22±0.39)×10−5 where the uncertainties are statistical, systematic and from the branching fraction of the normalization channel B−→D+π−π−, respectively. An amplitude analysis of the resonant structure of the B−→D+K−π− decay is used to measure the contributions from quasi-two-body B−→D∗0(2400)0K−, B−→D∗2(2460)0K−, and B−→D∗J(2760)0K− decays, as well as from nonresonant sources. The D∗J(2760)0 resonance is determined to have spin 1.
Im Titel sind "-" und "+" hochgestellt
Gesehen am 02.08.2021
LHCb Collaboration: R. Aaij, M. Adinolfi, B. Adeva, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, S. Braun, M. Britsch, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, C. Färber, M. Fontana, E. Gersabeck, L. Grillo, O. Grünberg, X. Han, S. Hansmann-Menzemer, M. Heß, A. Jaeger, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, S. Neubert, M. Neuner, T. Nikodem, M. Schmelling, P. Seyfert, M. Stahl, U. Uwer, M. Vesterinen, C. Voß, R. Waldi, S. Wandernoth, D. Wiedner, A. Zhelezov [und viele weitere]